Impairment of the Cell Wall Ligase, LytR-CpsA-Psr Protein (LcpC), in Methicillin Resistant Staphylococcus aureus Reduces Its Resistance to Antibiotics and Infection in a Mouse Model of Sepsis - Li, Fan; Zhai, Dongsheng; Wu, Zhaowei; Zhao, Yan; Qiao, Dandan; Zhao, Xin (Frontiers in Microbiology, 2020)
Staphylococcus aureus is a major opportunistic pathogen, infecting animals and human beings. The bacterial cell wall plays a crucial role in antimicrobial resistance and its infection to host cells. Peptidoglycans (PGs) are a major component of the cell wall in S. aureus, which is heavily decorated with wall teichoic acids (WTAs) and capsular polysaccharides (CPs). The ligation of WTAs and CPs to PGs is catalyzed by LCP family proteins, including LcpA, LcpB, and LcpC. However, the involvement of LcpC in antimicrobial resistance of S. aureus and its infection to host cells remains unknown. By creating the LcpC-knockout strains, we showed that the deficiency in LcpC decreased the antimicrobial resistance to β-lactams and glycopeptides and impeded the binding to various epithelial cells. These changes were accompanied by the morphological changes in bacterial cell wall. More importantly, the knockout of LcpC significantly reduced the pathogenicity of methicillin-resistant S. aureus (MRSA) in mice. Our results suggest that LcpC might be an appealing target for developing a therapeutic approach against MRSA infections.